2016
DOI: 10.1270/jsbbs.66.328
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drought stress on the leaf relative water content and tuber yield of a half-sib family of ‘Katahdin’-derived potato cultivars

Abstract: Drought tolerance in plants is a complex trait involving morphological, physiological, and biochemical mechanisms. Hundreds of genes underlie the response of plants to the stress. For crops, selecting cultivars that can produce economically significant yields under drought is a priority. Potato (Solanum tuberosum L.) is considered as drought sensitive crop, although cultivar-dependent differences in tolerance have been described. Cultivar ‘Katahdin’ possesses many appropriate characteristics and is widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
102
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 23 publications
17
102
1
4
Order By: Relevance
“…These significant differences in phenotypic response under drought stress suggests that tolerant abilities of Korean native plants vary. Similar results were obtained in the research that 'Katahdin', a drought tolerant genotype of potato, showed higher yields than others under drought condition by stopping watering (Soltys-Kalina ., 2016). Therefore, the method to treat drought by stopping watering can be used to screen drought tolerant plants.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…These significant differences in phenotypic response under drought stress suggests that tolerant abilities of Korean native plants vary. Similar results were obtained in the research that 'Katahdin', a drought tolerant genotype of potato, showed higher yields than others under drought condition by stopping watering (Soltys-Kalina ., 2016). Therefore, the method to treat drought by stopping watering can be used to screen drought tolerant plants.…”
Section: Introductionsupporting
confidence: 86%
“…3 D-F RWC and RWL are related to drought tolerance and these parameters have also been proposed as more important indicators of water status in plants such as wheat, potato and peanut. (Farshadfar and Ghasem, 2015;Keles ., 2004;Soltys-Kalina ., 2016;Arunyanark ., 2008). These previous studies allow us to measure the water status parameters on drought stress.…”
Section: Estimation Of Soluble Reducing Sugarmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland, an increase in the frequency of soil drought has been observed recently (http://www.climateadaptation.eu/poland/agriculture‐ and‐horticulture/) that resulted in severe loss of tuber yield by 7%–45%. The modern potato cultivars are highly sensitive to soil drought (Sprenger et al., ) although variability in response to soil drought is observed (Monneveux et al., ; Sołtys‐Kalina, Plich, Strzelczyk‐Żyta, Śliwka, & Marczewski, ; Sprenger et al., ). The relatively limited progress made in improving the potato drought resistance seems to be caused by a poor knowledge of the mechanisms responsible for drought resistance in the potato and in consequence, lack of effective methods for selection (Monneveux et al., ; Sprenger et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have provided large quantities of reports on the drought resistance of plants, mainly focus on the following fields: the condition of plant growth (Khalid, 2006;Rodriguez et al, 2005;Zhang et al, 2015b), the anatomical structures of leaves (Kutlu et al, 2009;Zhang et al, 2015a), the change of protective enzyme activity (Guan et al, 2015;Weng et al, 2015;Yang et al, 2014b) and the water metabolism and osmotic adjustment of plant tissue (Fu et al, 2016;Soltys-Kalina et al, 2016;Yasmin et al, 2013). With the constant development of more advanced apparatus for research, photosynthesis and chlorophyll fluorescence have also been applied in studies on the drought resistance of plants (Elsheery and Cao, 2008;Hassan, 2006;Liu et al, 2015;Ohashi et al, 2006;Zhang et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%